Evaluation of Labour Law Regulations to Protect Family-to-Business Relationships in The Terms of Social Policy - Merve Çiloğlu Yörübulut (Sosyal Siyaset Konferansları Dergisi)
Family is an ancient institution that provides humanity shelter from birth to death. The family institution, which has been affected by the fractures throughout history, has continued to exist by adapting. However, this adaptation process has also brought about changes in the structure of families. In postmodern societies, the family, like many other phenomena, faces many threats while being rebuilt on an ambiguous basis. Among the threats to by the family, the central position of the concept of work in social functioning is important. The concept of work lies at the centre of postmodern societies and is critically important. In this manner, where people primarily express themselves through their positions in working life, with technological developments, they become mentally integrated even though they are physically outside the work area. Protecting the family institution, which is an actor in social policy, is only possible by protecting it in working life. The most effective policies that can protect the family during working life can be produced through labour law regulations, which are also an important tool in social policy. This study highlights the need to protect the family in working life, examines the regulations that protect the family in labour law, identifies the issues that need to be protected, and offers suggestions for more effective protection.